Long-term maintenance rate fertilisation increases soil bacterial-archaeal community diversity in the subsoil and N-cycling potentials in a humid crop season - Pin Viso, Natalia Daniela; Ortiz, Jimena; Maury, Mariana; Frene, Juan Pablo; Iocoli, Gastón Alejandro; Lorenzon, Claudio Antonio; Rivarola, Maximo Lisandro; García, Fernando O.; Gudelj, Vicente Jorge; Faggioli, Valeria Soledad (Elsevier, 2024)
Among agronomical practices, fertilisation greatly influences soil microbial diversity and functionality and severely disturbs the global nitrogen (N) cycle. In this study, we assessed the effect of 16 years of mineral fertilisation (NPS) on soil bacterial-archaeal communities in a no-tillage experiment in a humid climate season. We used 16S rRNA amplicon sequencing and functional prediction of marker genes involved in the N cycle at two soil depths (0–5 and 5–10 cm). Samples were taken after soybean harvest in a wheat/soybean-maize crop sequence. At both soil depths, fertilisation increased the abundance of Proteobacteria while reducing the abundance of Verrucomicrobiota. Indicator species analyses revealed that MB-A2–108 (Actinobacteriota) and Nitrososphaeraceae (Archaea) were indicators of the low fertiliser rates at 0–5 cm. Instead, Rokubacteriales (Methylomirabilota) and Nitrolancea (Chloroflexi) were indicators of low and high rates, respectively, at 5–10 cm. Biological N–fixation genes (nifA, nifV nifHD1, and nifHD2) showed an inconsistent response depending on the soil depth. Yet, the high abundance of nifA revealed the presence of N-fixing microorganisms even at high levels of N fertilisation. The predominance of genes involved in the dissimilatory (nirB and nirK) and assimilatory (nirA) reduction of nitrate was steadily found at higher fertilisation. Given that the predecessor crop was a legume that did not receive N, our results revealed the substantial legacy of long-term N inputs on soil bacterial-archaeal diversity and N-cycling genes that might have been umpired by the current humid conditions.